On the concept of criminal offenses in the field of informatization and communication - Bizhanova, A.R.; Meyrbekova, G.B.; Zhunіsova G.A. (Bulletin of the Karaganda University “Law Series”, 2021)
The problem of ensuring the security of computer information and technologies, including criminal legal means, is today one of the most acute in many developed countries of the world. Computers, their systems, and networks are especially often used in industry and business. Enterprises suffer heavy losses due to various computer attacks and failures. The global computer network Internet has evolved from an academic re[1]source to a commercial environment where it is important to ensure security and prevent possible attacks on developing relationships. The purpose of the study is to consider the issue of legal regulation of cybercrime by domestic and foreign legislation and to solve terminological problems. As a result of the study, the concept of criminal offenses in the field of information technology is clarified. The authors of the article consider the state and danger of cybercrime in Kazakhstan. Given that the criminal offenses in Chapter 7 of the Criminal Code of the Republic of Kazakhstan cover the areas of information technology, it is proposed to rename the title of the chapter.